Electrodeposition of PANI-NiO as Electrode for Deionization K+ and Cl- - Auliya, Annisa; Deswara, Raka; Paristiowati, Maria; Budi, Setia (Chemistry and Materials, 2022)
This study aims to synthesize thin film of polyaniline-nickel oxide (PANI-NiO) as an electrode in capacitive deionization (CDI) technology. Thin film PANI-NiO were synthesized by electrodeposition method with different applied potentials. The FTIR spectrum and XRD pattern confirmed that PANI-NiO has been successfully synthesized. Based on the SEM-EDX data, PANI-NiO has a tightly stacked granular morphology, which consist of Fe, Cr, S, Ni, O, and C elements. Based on experimental results, the highest capacitance come from PANI-NiO 1.25 V with a value of 475.24 F/g. PANI-NiO 1.25 V also has a small resistance, which is 13.55 Ω. Salt reduction efficiency test for PANI-NiO 1.25 V also shows the highest salt reduction efficiency compared to other electrodes. Owing to its high capacitance, low charge transfer resistance, and high salt reduction capacity, the PANI-NiO prepared at 1.25 V might be a potential material to be developed for the electrolyte deionization application.